Investigation of circular based micropump diffuser - Johari, Bar Azwar (2010)
This thesis deal with the investigation of circular based piezoelectric micropump diffuser, fabrication and testing of the liquid flow rate that flow in the micropump. It is made emphasize on the development of piezoelectric micropump. Its layout is very different from other conventional micropump that has only three main parts. The prototype is modeled using SOLIDWORK and flow analysis of the model was using COSMOS and Fluent. The quantitative analysis done have determined the effect of differential diffuser angle to the outlet flow rate of water. For the fabrication purpose are to determined real flow rate to the outlet that has been compared with Fluent analysis flow rate. The objective of material selection was to reduce fabrication cost without reducing the micropump functional performance and efficiency. The type of piezoelectric circuit was the simplest design that required. Simple circuits were chosen as it easier to troubleshoot and provide more reliability in executing motion compared to complex coding. From COSMOS simulation, the micropump flow motions of liquid are smooth and functional. From Fluent simulation, the result comparable as calculated by the theory. Guide by preliminary result, a handmade fabrication is carried out to create a prototype to show how this innovative circular based micropump produce flow liquid from inlet to outlet diffuser, the other facting factor that can control the flow rate, the pulse in functioned and the flow motions are performed. The real testing is carried out resulted were tabulated. The experimental results are compared with the simulated results and the resulted are acceptable.